Identification of the Direction and Strength of Relationship between Complaints of Musculoskeletal Disorders (MSDs) to Smoking Habits and Repetitive Movements of Informal Workers in Surabaya, Indonesia Using Spearman Correlation Test Methods - Annisa Dwinda Shafira1, Genduk Lintang Rusmawarda2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The right statistical test to find out the relationship between variables that have ordinal data scale is a spearman correlation test. Spearman correlation shows how strong the relationship and the direction of the relationship between variables. The increasing muscle complaints have a close relationship with smoking habits. The longer and the higher the frequency of people smoke, the smaller the lung capacity. It then results in a decrease in the lung ability to consume oxygen. It also causes one more easily tired when carrying out tasks that require exertion. In addition, complaints due to repetitive movements occur because the muscles continuously receive workload pressure without a chance for relaxation. This condition triggers the occurrence of nerve swelling which will cause pain in the musculoskeletal area. This is an observational study with a cross sectional design. The study used a total sampling population of 12 workers. Spearman correlation is used to examine the strength and direction of the relationship between the dependent variable, MSDs complaints, an ordinal data scale, with independent variables, smoking habits and repetitive movements. This study found that smoking habits and the level of complaints of MSDs in the shelf frame bending workers have fairly strong, positive and unidirectional relationship with correlation coefficient value of 0.357. It also found that repetitive movements and complaint levels MSDs have a positive and perfect relationship with the correlation coefficient value of 1,000.